2018
DOI: 10.1371/journal.pone.0202647
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of HIV cure research among people living with HIV in Australia

Abstract: Participation in HIV cure-related clinical trials that involve antiretroviral treatment (ART) interruption may pose substantial individual risks for people living with HIV (PLHIV) without any therapeutic benefit. As such, it is important that the views of PLHIV are considered in the design of HIV cure research trials. Examining the lived experience of PLHIV provides unique and valuable perspectives on the risks and benefits of HIV cure research. In this study, we interviewed 20 PLHIV in Australia about their k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 39 publications
(51 reference statements)
1
49
0
Order By: Relevance
“…Our findings about RV411 participants’ motivations extend results from our previous study of 12 participants in another SEARCH HIV remission trial with an experimental agent and ATI , and studies that ask PLWHIV about hypothetical decision making for similar trials . We found that very early HIV diagnosis created a sense of having “special bodies” for research that offered the potential for reciprocal benefit to self and others, and that treatment interruption was perceived as both a potential personal risk and benefit; both themes were reproduced here.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings about RV411 participants’ motivations extend results from our previous study of 12 participants in another SEARCH HIV remission trial with an experimental agent and ATI , and studies that ask PLWHIV about hypothetical decision making for similar trials . We found that very early HIV diagnosis created a sense of having “special bodies” for research that offered the potential for reciprocal benefit to self and others, and that treatment interruption was perceived as both a potential personal risk and benefit; both themes were reproduced here.…”
Section: Discussionmentioning
confidence: 99%
“…Curing HIV has become a global strategic priority [1][2][3][4], but clinical trials may present significant potential risks to the health of trial participants and raise considerable ethical concerns [1,5,6]. Community engagement has been shown to be effective in collecting community input to address ethical issues in health research, including HIV cure research [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Community engagement is the process of empowering people to become actively involved in defining and influencing issues that concern them [8,9]. Community engagement within HIV cure research can enhance communication between researchers, patients, and the community [10,11], encourage ethical trial participation [1,6,12], and assist in post-trial implementation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The science of “treatment as prevention” (TasP) has been translated into a hugely successful communications campaign of “Undetectable = Untransmittable” or “U = U.” It is important to examine how communities understand viral suppression and “U = U” in relation to HIV cure research (and cure itself), and how this affects their priorities. For example, there can be an inherent tension in cure studies utilizing ATIs that precipitate rebounds in viraemia and the U = U concept for sexual transmission of HIV . We make a distinction between 1) durable viral suppression from using ART as prescribed and having longstanding clinically undetectable viral load test results versus 2) sustained ART‐free HIV remission meaning longstanding undetectable circulating replication‐competent HIV by research‐grade testing without continued use of ART.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies assessing willingness to participate in HIV cure research, risk acceptability, barriers and motivators to participation, as well as perceptions, beliefs, needs and concerns of potential study participants around the world [26,40,48,51,[61][62][63][64][65][66]. Early findings indicate that there likely will be disagreements between stakeholders about what constitutes acceptable risks for HIV cure studies, and a triangulation of these views will be necessary [48,65].…”
Section: Supportive Bssr: Strengthening the Design And Outcomes Of mentioning
confidence: 99%